The Impact of Pyroglutamate: Sulfolobus acidocaldarius Has a Growth Advantage over Saccharolobus solfataricus in Glutamate-Containing Media. (24th April 2019) - Vetter, Anna M.; Helmecke, Julia; Schomburg, Dietmar; Neumann-Schaal, Meina
Abstract : Microorganisms are well adapted to their habitat but are partially sensitive to toxic metabolites or abiotic compounds secreted by other organisms or chemically formed under the respective environmental conditions. Thermoacidophiles are challenged by pyroglutamate, a lactam that is spontaneously formed by cyclization of glutamate under aerobic thermoacidophilic conditions. It is known that growth of the thermoacidophilic crenarchaeon Saccharolobus solfataricus (formerly Sulfolobus solfataricus ) is completely inhibited by pyroglutamate. In the present study, we investigated the effect of pyroglutamate on the growth of S. solfataricus and the closely related crenarchaeon Sulfolobus acidocaldarius. In contrast to S. solfataricus, S. acidocaldarius was successfully cultivated with pyroglutamate as a sole carbon source. Bioinformatical analyses showed that both members of the Sulfolobaceae have at least one candidate for a 5-oxoprolinase, which catalyses the ATP-dependent conversion of pyroglutamate to glutamate. In S. solfataricus, we observed the intracellular accumulation of pyroglutamate and crude cell extract assays showed a less effective degradation of pyroglutamate. Apparently, S. acidocaldarius seems to be less versatile regarding carbohydrates and prefers peptidolytic growth compared to S. solfataricus . Concludingly, S. acidocaldarius exhibits a more efficient utilization of pyroglutamate and is not inhibited by this compound, making it a better candidate for applications with glutamate-containing media at high temperatures.